Interpretive trail planning at Biro Tata Negara forest, Kundasang - Ahidi, Mohd. Iqbal Syrazi (2016)
There are many elements of natural resources with high potential to be used as an element of interpretation along the interpretive trail in Biro Tata Negara Forest areas. This study was conducted to plan the development of interpretive trails that will be used as outdoor recreational activities for visitors to BTN. The planning to establish an interpretive trail is that the benefits can be provided for visitors such as general knowledge and information, satisfaction and authentic experience. An inventory of interpretive trails was conducted using the sampling point’s method of the trail route to locate and identify all natural resources or elements of interpretive involving five categories: biophysical characteristics, water resources, flora, fauna and scenery / weather conditions. Next, all information about elements that have been identified will be analyzed and subsequently developed an interpretation trail complete with themed stations in BTN Forest areas. The results of the inventory of recreational resources show that there are seven stations along with the appropriate theme. The purpose of the theme of each station is to get the attention on the visitors and at the same time create awareness with information and knowledge about nature. Next, the positive results will come out such as the awareness, conservation and preservation about our forest.